"Non‐Representational Theory for the Uninitiated: Come JUMP with me!". Issue 1 (16th January 2013) - Somdahl‐Sands, Katrinka
Abstract The article/performance is a 13 minute performance/presentation/film investigating the role of the subject in nonrepresentational theory. The piece is a discussion of Non‐Representational Theory, identity and dance. In particular, it I describe how I, as a feminist/political geographer who writes about dance, (so I fell in with Non‐Representational Theory by association), came to understand what all the fuss was about with NRT by finally placing it in my own body, and also came to an accommodation between NRT as a theory and my own interest in feminist political praxis. The foundation of the work is a film commissioned by the author/performer of JUMP! by the BodyCartography Project for the SCUBA National Touring Network for Dance in Philadelphia March 2010. On top of this film, I narrate my experience in understanding what NRT is, how I figured out how an "I" could be a "trans‐identity", and how that understanding can be used for political change. Because I am, in effect, speaking to my audience/reader I ask them to DO things as I speak to further their experiential understanding of NRT (which by its nature is experiential).